Penetapan Skala Industri Batik Rumahan Menurut Kriteria Lokal: Studi di Desa Jarum, Kabupaten Klaten - Handayani, Widhi; Hunga, Arianti Ina Restiani; Kristijanto, A Ign (Institut Pertanian Bogor, 2017)
Bayat Sub-district of Klaten Regency has been supplying batik to Yogyakarta and Surakarta since the 1960’s. The role of Bayat as a batik provider is inseparable from Jarum village, which was officially established as a tourism village by the Government of Klaten Regency in 2014. Considering that batik is produced under Putting Out System (POS) which employs home workers, the industrial scale criteria applied to formal industry is less appropriate if it will be applied to batik home-industry as a micro-small scaled industry. This research was conducted to describe the profile of batik industry in Jarum village as well as arrange criteria used by Jarum people to determine the scale of batik industry. This qualitative research data was collected by interview, observation, documentation, and literature study. The results showed that there were 19 industries producing batik cloth, 10 industries producing batik woodcraft, 1 industry producing batik T-shirt, and 1 industry producing batik painting. Based on local perception, 7 industries were categorized as large, 13 industries were categorized as moderate, and 11 industries were categorized as small. The criteria used to establish the industrial scale were production scale, number of employees, and marketing reach. Only 5 industries found to apply natural colorants for batik clothes production, while synthetic dyes were applied broadly for batik clothes, batik T-shirt, batik woodcraft, and paintings. Natural colorants less desirable by batik Juragans who use synthetic dyes because the application of natural dyes will prolong the production, limits the scale of production, tend to shows uncontrolled quality, and more difficult to sell.